The influence of public artworks with children's painting characteristics on urban culture and public space - Na, Luo; Ibrahim, Rahinah; Zainal Abidin, Sazrinee (Kosmos Publishers, 2021)
With the rapid development of society, the urban environment is facing great challenges. It is necessary to carry out public artworks design in urban public spaces. Integrating public art design into urban cultural construction can build a good urban image. The purpose of this study is to explore the impact of public artworks with children's painting characteristics on urban culture, and public space. This study presents a preliminary literature review to understand the background knowledge of public space. It includes an analysis of the relationship between public artworks, urban culture and public space. The purpose is to explore the impact of public works of art with the characteristics of children's painting on people's happiness in public space. The research results include analyzing the background knowledge of public space, exploring the relationship between public art and urban culture, and analyzing the impact of public artworks with children's painting characteristics on the public space and people's happiness. They contribute to the development of a theoretical framework for improving the quality of public space and urban cultural connotation through excellent public artworks in order to stimulate public happiness.This research can help artists create more high-quality public artworks for the urban environment, so as to arouse people's happiness. At the same time, the research helps to build a good public space and urban image and to promote the development of the city.